Comparison of Reverse Transcriptase Loop-Mediated Isothermal Amplification and Reverse Transcriptase Polymerase Chain Reaction for Detection of Prostate Specific Antigen - Almasi, Mohammad Amin; Esmaili, Marya (Basic and clinical cancer research, 2019)
Background: Research shows that prostate cancer ranks second among the top five most common cancers in men. It has been confirmed that when circulating Prostate Specific Antigen (PSA) transcripts are successfully detected, prostate cancer cells can be diagnosed at an early stage. A reverse transcriptase loop-mediated isothermal amplification (RT-LAMP) assay was developed and compared to reverse transcriptase polymerase chain reaction (RT-PCR) assay for detection of PSA. Methods: 47 patients, including 30 patients with prostate cancer, 15 with Benign Prostate Hyperplasia (BPH) and 2 healthy subjects as negative controls were included in this study. The prostate cancer cell lines (PC3 and LNCaP) of two patients were included in the study as positive controls. Next, RNA was extracted from fresh samples and a first strand cDNA synthesis kit was applied for the synthesis of cDNA. The human prostate specific antigen gene was used to design specific primers. Results: The results indicated that the control subjects and participants suffering from BPH were not positive. 13 out of 15 (86.6%) patients suffering from localized cancer were PSA positive. PSA positive results were observed among all 15 metastatic patients and positive controls (100%). RT-LAMP is an advantageous method because it is highly sensitive (1000-fold), quite cheap, user-friendly, and safe; in addition, it can be quickly performed by visual detection using GineFinderTM dye in a water bath. Conclusion: RT-LAMP technique can be simply and reliably applied with the aid of basic instruments, and its results can be visually inspected in laboratory studies.